SOCIALLY RESPONSIBLE MARKETING IN TOURISM AND HOSPITALITY SECTOR - Mathur, Dr. Parul; *, Aashish (IJRDO - Journal of Business Management, 2016)
In today’s rapidly changing tourism market, it is getting more and more difficult for a destination to be competitive on the global level. Hotel companies, as well as tour operators have a very important role in creating the tourism product. Tourism companies should be able to create the tourism product whilst operating in a responsible way. With the implementation of a socially responsible business practice, tourism companies contribute to the achievement of sustainable tourism and, consequently, to the achievement of sustainable developmentSocially responsible marketing has only recently risen to prominence as a serious discipline, and its future remains desperately uncertain. Too narrow in its aims to engage management attention, too broad and unquantifiable to be taken seriously by the financial community, and just woolly enough to be exploited by charlatans and opportunists. Socially responsible marketing is important because businesses are based on trust and foresight. Establishing and keeping trust with customers, communities and regulators isn‟t simple and can be easily damaged or lost. To be successful in the long-term, companies need to think beyond what‟s affecting them today to what‟s going to happen tomorrow. This isn‟t just about addressing changes to technology or the needs of customers, but also taking into account alterations in social, environmental and governance issues.